Factors affecting the students' choice of librarianship as a career - Buenrostro, Juan C. (1977)
This study is about the factors affecting the choice of librarianship as a career by undergraduate library science students. Two-hundred and twenty six third year and fourth year library science students were used as subjects in this study. They were purposively selected from nine library schools in Metro Manila during the first semester 1977-1978.